The economics of money - Day, A. C. L. (London, Oxford University Press, 1959)
The book examines the issue of money and banking system in Great Britain. It also analyzes the balance of payment and trade as well as that of International Monetary experience in the post-war world.
includes index
usc 30/6/17
Loans
Keywords: Money; Banks and banking; Great Britain